2022
DOI: 10.1093/humrep/deac058
|View full text |Cite
|
Sign up to set email alerts
|

Sperm selection with hyaluronic acid improved live birth outcomes among older couples and was connected to sperm DNA quality, potentially affecting all treatment outcomes

Abstract: STUDY QUESTION What effects did treatment using hyaluronic acid (HA) binding/selection prior to ICSI have on clinical outcomes in the Hyaluronic Acid Binding sperm Selection (HABSelect) clinical trial? SUMMARY ANSWER Older women randomized to the trial’s experimental arm (selection of sperm bound to immobilized (solid-state) HA) had the same live birth rates as younger women, most likely a result of better avoidance of sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 91 publications
0
27
0
1
Order By: Relevance
“…Conversely, when oocytes from greater quality—because they come from donors—were involved, ICSI outcomes were better and it was thus easier to determine the influence of sperm DNA integrity on embryo development. This would not obviously exclude that sperm DNA fragmentation could worsen ICSI outcomes if gametes from male and female patients are combined, as suggested by previous studies [ 13 , 59 , 63 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, when oocytes from greater quality—because they come from donors—were involved, ICSI outcomes were better and it was thus easier to determine the influence of sperm DNA integrity on embryo development. This would not obviously exclude that sperm DNA fragmentation could worsen ICSI outcomes if gametes from male and female patients are combined, as suggested by previous studies [ 13 , 59 , 63 ].…”
Section: Discussionmentioning
confidence: 95%
“…Hence, one may thus reasonably posit that the differences in the origin of oocytes could be one of the reasons to explain the inconsistencies in the literature about the actual influence of sperm DNA integrity on ICSI outcomes, particularly when infertile patients are committed [ 57 , 58 ]. In effect, while a previous work including infertile males showed that the male factor had a great impact on pregnancy outcomes when oocytes from infertile or older women were used [ 14 , 59 ] and another study using donor oocytes reported an association between sperm genotoxic damage and ICSI outcomes [ 60 ], other researchers concluded that sperm DNA damage in infertile males was not associated to ICSI outcomes, regardless of the oocyte origin [ 17 ]. Whilst these three opposite results clearly reflect the controversy on the topic, one has to note that all them were conducted in infertile males; yet, the current study is the first to approach the matter in a double donation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…An important example of this published during the final stages of proofing this manuscript, is a highly relevant paper, specifically pertaining to the previously published clinical HABSelect trial by Miller et al (2019) [31], asking what effects HAB select ahead of ICSI had on clinical outcomes. In brief, the findings were that older women who were randomised to the experimental arm of this trial (i.e., sperm selected through HA binding) had live birth rates not significantly different from that of younger women [98]. The authors postulate that this is probably due to "better avoidance" of sperm that had DNA damage.…”
Section: Future Approaches By the Clinic And The Hfeamentioning
confidence: 93%
“…Meta analyses have also concluded current evidence is inadequate to exclude adverse effects or differentiate the efficacy of SpermSlow versus PICSI HA binding systems (53). On the contrary, recent re-analysis of data from a parallel, two-group, randomized trial (i.e., HABSelect) has now reported that the use of PICSI is positively associated with a reduction in the rate of miscarriages, particularly in the subset of women aged over 35 (39,55). Such an effect has been attributed to PICSI selection of spermatozoa with reduced levels of DNA damage.…”
Section: Sperm-hyaluronic Acid Bindingmentioning
confidence: 99%